Pengembangan Kurikulum Pendidikan Jasmani Berbasis Pendekatan Desain untuk Menguatkan Profil Pelajar Pancasila (P5) - Suardi; Ayu Raihani (Design Journal, 2024)
Designing the right physical education curriculum can build a holistic learning atmosphere for students. The purpose of the study was to develop a physical education curriculum that combines a design approach with the aim of improving the profile of Pancasila students (P5). Classroom action research developed learning, where learning modules were used when doing physical activities to foster Pancasila values. The results of the study showed that the use of a design approach in the physical education curriculum can increase student interest, social skills and foster awareness of Pancasila values. Therefore, it is known that the curriculum does not limit itself to the physical side but also discusses the emotional and social sides that help facilitate holistic character development. The results of the study are expected to help develop physical education curricula in schools and can be used as a reference for a practice-based approach that uses design in the pedagogical approach